The association between lung cancer incidence and ambient air pollution in China: A spatiotemporal analysis - Guo, Y.; Zeng, H.; Zheng, R.; Li, S.; Barnett, A.; Zhang, S.; Zou, X.; Huxley, Rachel; Chen, W.; Williams, G. (2016)
© 2015 Elsevier Inc. Background: China is experiencing more and more days of serious air pollution recently, and has the highest lung cancer burden in the world. Objectives: To examine the associations between lung cancer incidence and fine particles (PM2.5) and ozone in China. Methods: We used 75 communities' data of lung cancer incidence from the National Cancer Registration of China from 1990 to 2009. The annual concentrations of fine particles (PM2.5) and ozone at 0.1°×0.1° spatial resolution were generated by combing remote sensing, global chemical transport models, and improvements in coverage of surface measurements. A spatial age-period-cohort model was used to examine the relative risks of lung cancer incidence associated with the air pollutants, after adjusting for impacts of age, period, and birth cohort, sex, and community type (rural and urban) as well as the spatial variation on lung cancer incidence. Results: The relative risks of lung cancer incidence related to a 10µg/m3 increase in 2-year average PM2.5 were 1.055 (95% confidence interval (CI): 1.038, 1.072) for men, 1.149 (1.120, 1.178) for women, 1.060 (1.044, 1.075) for an urban communities, 1.037 (0.998, 1.078) for a rural population, 1.074 (1.052, 1.096) for people aged 30-65 years, and 1.111 (1.077, 1.146) for those aged over 75 years. Ozone also had a significant association with lung cancer incidence. Conclusions: The increased risks of lung cancer incidence were associated with PM2.5 and ozone air pollution. Control measures to reduce air pollution would likely lower the future incidence of lung cancer.